Associations Between Cancer Screening Behavior and Complementary Medicine Use: Results of a National Cross-Sectional Survey of 9151 Australian Women. (September 2018) - Frawley, Jane Elizabeth; McIntyre, Erica; Sibbritt, David; Wardle, Jon; Schloss, Janet; Lauche, Romy; Adams, Jon
Introduction: Complementary medicine (CM) use has been found to influence the uptake of conventional cancer treatment. This study examines associations between CM use and cancer screening rates.Methods: Women aged 62 to 67 years from the Australian Longitudinal Study on Women's Health were surveyed regarding their use of cancer screening initiatives. Associations between cancer screening behavior and visits to CM practitioners were analyzed.Results: Of the 9151 women, 9049 (98.9%) completed questions about cancer screening. A total of 65.1% of women had received a clinical skin examination, 54.3% colorectal cancer screening, 56.2% Pap test (within past 2 years), 83.3% mammogram (within past 2 years), 55.8% clinical breast examination, and 55.8% had conducted breast self-examination. Women who had consulted a massage therapist were more likely to undergo clinical skin examination ( P = .002), clinical breast examination ( P = .018), and mammogram ( P = .001). Women who had consulted a chiropractor were more likely to undergo a clinical skin examination ( P = .001), colorectal cancer screening ( P = .020), and mammogram ( P = .011). Women who had consulted an acupuncturist were more likely to undergo colorectal cancer screening ( P = .019), and those who consulted with an osteopath were more liable to have a Pap test ( P = .049).Conclusion: Women who visit CM practitioners are more likely to participate in cancer screening initiatives. Research is required to understand the current and potential role that CM practitioners (can) have as public health advocates, recommending preventative health measures such as cancer screening. Such an examination will help ensure optimal screening utilization and effective, timely care for all cancer patients.